Antimony sulfide (Sb2S3) thin films by pulse electrodeposition: Effect of thermal treatment on structural, optical and electrical properties. (15th March 2016) - Avilez Garcia, R.G.; Meza Avendaño, C.A.; Pal, Mou; Paraguay Delgado, F.; Mathews, N.R.
Abstract: Antimony sulfide films have been deposited by pulse electrodeposition on Fluorine doped SnO2 coated glass substrates from aqueous solutions containing SbCl3 and Na2 S2 O3 . The crystalline structure of the films was characterized by X-ray diffraction, Raman spectroscopy and TEM analysis. The deposited films were amorphous and upon annealing in nitrogen/sulfur atmosphere at 250 °C for 30 min, the films started to become crystalline with X-ray diffraction pattern matching that of stibnite, Sb2 S3, (JCPDS 6-0474). AFM images revealed that Sb2 S3 films have uniformly distributed grains on the surface and the grain agglomeration occurs with annealing. The optical band gap calculated from the transmittance and the reflectance studies were 2.2 and 1.65 eV for as deposited and 300 °C annealed films, respectively. The annealed films were photosensitive and exhibited photo-to-dark current ratio of two orders of magnitude at 1 kW/m 2 tungsten halogen radiation.